Optical monitoring of curing process of concrete with plastic optical fibers - Ferreira, L.
In this paper we propose an optical monitoring scheme for the concrete curing process, based on plastic optical fibers. The proposed sensor intend to use the scattering properties of the light on a plastic optical fiber, enhanced by the use of grooves, to monitor the water content in the cement paste, and therefore to be used in the control of the cure process. The sensor can be used in field to monitor the concrete curing process and as a result optimize the construction phase.